Establishing the correlation between R353Q polymorphism and haemostatic markers in a black elderly community of Sharpeville Gauteng Province South Africa. - Rodrigue, Tagne Wambo Joseph (Vaal University of Technology, 2019)
Background: In a group of the elderlies (older person) in Sharpeville, Gauteng, South Africa, the majority live in poverty with a poor nutritional status. This makes them susceptible to develop infectious diseases as well as the risk of Chronic Diseases of the Lifestyle (CDL) such as cancer, diabetes, heart attack, obesity and hypertension. One of the most constant features of aging is the progressively elevated levels of coagulation factors such as FVII, fibrinogen, and impairment of fibrinolysis might play a role in the ageing process. These are associated with increased susceptibility to Cardiovascular diseases (CVD) commonly found. An association between elevated levels of FVII and R353Q polymorphism has been established as a risk factor for CVD. This genetic polymorphism R353Q characterizes the substitution in the exon 8 of the FVII gene of guanine-to-adenine, which results in the replacement of arginine (R) by glutamine (Q) in codon 353 of the F7gene. Objectives: The aim of this study was to evaluate the prevalence of R353Q polymorphism in correlation with haemostatic markers within an urban elderly community in South Africa. Method: This study was ethically approved, and it is an experimental research design on the prevalence of R353Q polymorphism in correlation with homeostatic status (Factor VII, Fibrinogen and PAI-1). The study was done in a black elderly population living in the Vaal triangle region of Sharpeville, attending a day care center, who gave consent to participate in the study. A purposely selected sample of 102 subjects, who met the inclusion criteria were used. The homeostatic status was measured by factor VII and fibrinogen measuring coagulation and PAI-1 measuring fibrinolysis. Results: The prevalence of R353Q genetic polymorphism was established in 14.5% of the sampled population. The prevalence of the RQ (AG) genotype was determined in the sample population with 6.5 % of elevated factor VII levels, 7.8% of increased fibrinogen levels (coagulation) and 10.5 % of decreased levels of PAI-1. The R(A) allele, was detected in 1.3% of the sampled population of normal levels of FVII, fibrinogen and PAI-1. The dominant allele G(Q) was present in 76.3% of the sampled population. An imbalance haemostatic marker was established in the sampled population with 61% of elevated levels of factor VII, 70% of elevated levels of fibrinogen and 88% had a decreased level of PAI-1. Conclusion: The prevalence of R353Q polymorphism was established in this sample population, having an imbalanced haemostatic status of hypercoagulation (factor VII and fibrinogen) and imbalance fibrinolysis (PAI-1), which are strongly associated to CVDs.
M. Tech. (Department of Biotechnology, Faculty of Applied and Computer Sciences), Vaal University of Technology.
Keywords: Haemostatic markers; Polymorphism markers; Black elderly community; Dissertations, Academic -- South Africa.; Genetic polymorphisms.; Older people -- Diseases.